Resonance-sensitive professional vision. A qualitative study on teachers’ noticing practices - Steinwachs, Jens; Kalthoff, Justus; Reinold, Marcel (Frontiers in Education, 2025)
Teacher noticing is widely recognized as an important aspect of teachers’ competencies and professional development. Drawing on resonance pedagogy, we propose resonance-sensitive professional vision as a new theoretical concept to analyze teacher noticing practices, aiming to highlight often neglected criteria of instructional quality. Our study investigates patterns of noticing among biology teachers using reflexive thematic analysis on a comprehensive qualitative dataset. Stimulated by a video clip that authentically represents complex classroom interactions, 31 group discussions and nine individual interviews were conducted, involving a total of 115 pre-service and in-service biology teachers. Our analysis indicates that pre-service and in-service teachers often rationalize teaching and learning to the extent that they overlook instructional quality criteria emphasized by resonance pedagogy. Most notably, participants focus on the effective achievement of learning outcomes while neglecting the affective engagement of both students and teachers with the learning material. Additionally, their noticing patterns reveal an implicit conceptualization of teaching and learning as processes that are largely steerable and controllable. This perspective tends to ignore the importance of being open and responsive to students’ thoughts and navigating the inherent uncertainty of teaching and learning processes. We hypothesize that adopting a resonance-sensitive professional vision could enhance teachers’ job satisfaction, foster professional development, and contribute to a good professional life. In contrast, an over-rationalized vision may lead to frustration and increase the risk of long-term occupational dissatisfaction. Further studies are needed to explore the factors influencing professional vision and its relationship with job satisfaction.